PENGARUH IKLAN ONLINE MELALUI MEDIA FACEBOOK TERHADAP KEPUTUSAN PEMBELIAN PAKAIAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRUNOJOYO MADURA - Hening Ary Putra; - Suyono (Universitas Trunojoyo Madura, 2014)
The purpose of this study was to identify variables like stance on online advertising, online advertising recall in, and the frequency of clicks on online advertisements that influence purchasing decisions on the clothes Faculty of Economics and Business, Universitas Trunojoyo Madura either simultaneously or partially. The hypotheses are: Factors that influence purchasing decisions like stance on online advertising, online advertising recall in, and the frequency of clicks on online advertising significantly influence in clothing purchase decisions either simultaneously or partially. This research was conducted with quantitative methods where the population in this study were students of the Faculty of Economics and Business, Universitas Trunojoyo Madura and obtained a sample of 40 respondents taken using accidental sampling method by distributing questionnaires. Conclusions of this study were (1) simultaneously a significant relationship between the independent variables (attitude on online advertising, online advertising recall in, and the frequency of clicks on online ads) on purchase decisions clothing (2) partial, shows that vairabel attitude on online advertising and online advertising recall the positive and significant impact on purchasing decisions, except the variable frequency clicks on online ads are not positive and significant impact on purchasing decisions. (3) partial variable recall has the greatest influence on purchasing decisions clothing.